Proximal Tibial Fractures in the Pediatric Population - Tileston, Kali; Frick, Steven (The Journal of Knee Surgery, 2018)
Injuries about the proximal tibia are quite common in children. Understanding the mechanisms of injury and treatment strategies is imperative for practitioners caring for these patients. Similarly, appreciating the anatomy of the proximal tibia and the adjacent neurovascular structures can assist a practitioner in recognizing the potential associated risks following fracture. Patients with injuries about the proximal tibia require long-term follow-up, and knowledge of the natural history of these fractures is imperative.
Keywords: pediatric orthopaedics; trauma; physeal injury; proximal tibia fracture; Cozen fracture